“They tossed me up like a ball”: informal settlement residents’ experiences in accessing healthcare in Kampala, Uganda - Julia Dickson-Gomez; Kirsten Beyer; Arthur Kiconco; Ronald Anguzu; Agnes Nyabigambo (BMC Public Health)
Abstract Background Most urban dwellers (55%) in low- and middle-income countries (LMICs) live in informal settlements. Informal settlement dwellers have higher disease risk and poorer quality of life than residents of formal urban environments, yet they have less access to healthcare. Despite benefits of most international health aid delivered through Global Health Initiatives (GHIs) such as the WHO, USAID, and PEPFAR in rapidly addressing specific conditions such as HIV, TB, malaria, many GHI have created parallel structures to existing health systems. This paper examines the experiences residents of informal settlements have in trying to access basic healthcare in the context of global health aid. Methods In this community-based study, we conducted focus group interviews (FGI) among 165 residents of six purposively selected informal settlements in Kampala, Central Uganda. Participants were purposively sampled to reflect participant demographics such as gender and age, with separate groups for males, females, youth and refugees. FGI asked residents about settlement formation, community challenges, governmental and non-governmental responsiveness, and health service delivery. Interviews were audio-recorded, transcribed verbatim and translated as needed. Inductive and deductive coding were used to merge codes into a final codebook, identifying emergent sub-themes and overarching themes summarized with supporting quotes. Results Residents described barriers to accessing three separate healthcare systems: the public health system (national and regional referral hospitals and district health centers), the private health system, and the international donor healthcare system. Dimensions of affordability and approachability limited healthcare access in both the public and private systems, while most residents were excluded from disease-specific international donor funded care. The focus group interviews indicated that private healthcare systems have created incentives to draw resources away from already depleted public healthcare systems, further decreasing access to the most vulnerable. Conclusions Our study reveals important and substantial gaps in the current healthcare system in Uganda. The main perceived health system challenges were its affordability and ‘approachability’ among residents of informal settlements. GHIs drain resources from the national health system and neglect coverage for non-priority diseases. We call upon policymakers to re-prioritize and respond to these health system challenges.